COVID-19 extracellular vesicles display heterogeneity based on viral and host RNA expression: implications for host immune response - Juárez, Esmeralda; Vázquez-Pérez, Joel A; Carreto-Binaghi, Laura E; Martínez-Sanabria, Claudia A; Salgado-Cantú, Manuel G; Sarabia, Carmen; Herrera, María Teresa; Guzmán-Beltrán, Silvia; Gutiérrez-González, Luis H; González, Yolanda (Journal of leukocyte biology, 2025)
Viral RNA and miRNAs released by immune cells contribute to inflammation in COVID-19 patients. Here, we investigated the role of SARS-CoV2 RNA and host miRNAs carried within extracellular vesicles (EVs) in modulating inflammation. EVs were classified as positive or negative depending on their viral RNA cargo. To assess the function of viral RNA, EVs, and lipopolysaccharide (LPS) were used to stimulate whole blood samples from healthy subjects, and the secretion of 27 serum analytes was measured. EVs alone did not induce cytokines, chemokines, or growth factors. However, under LPS stimulation, (SARS-CoV2+) EVs increased IL-12 and decreased IL-13 secretion, while (SARS-CoV2-) EVs increased MIP-1α and IL-1β secretion. Host miR-19a-3p, -192-5p, -let-7c-5p, and -92b-3a were differentially expressed in association with viral RNA. EVs from COVID-19 patients exhibited differences in viral RNA and miRNA expression profiles that modulate LPS responses. This knowledge sheds light on the immunopathology of COVID-19.